Pre‐ and post‐bone marrow harvest anaemia is associated with lower CD34+ stem cell collection, high harvest volume and female gender. Issue 3 (5th March 2020) - Getta, Bartlomiej M.; Tong, Daochen; Deren, Stephanie; Huang, Gillian; Hogg, Megan; Collins, David; Bhattacharyya, Abir; Panicker, Shyam; Micklethwaite, Kenneth; Blyth, Emily; Bilmon, Ian; Kwan, John; et al.
Abstract: Background: Donor safety is paramount when performing bone marrow stem cell harvest. The incidence of full blood count (FBC) abnormalities among donors and variables associated with anaemia after marrow harvest are not well established. Aims: To describe the frequency of FBC abnormalities prior to bone marrow stem cell harvest and to identify variables associated with post harvest anaemia. Methods: Outcomes of 80 consecutive adult marrow harvests performed at our centre were analysed retrospectively. Results: FBC abnormalities were present in 28% of donors prior to marrow harvest with normocytic anaemia the most common abnormality in 13%. Reduced donor haemoglobin (Hb) was independently correlated with lower CD34+ cell count per kg of recipient body weight. Anaemia (Hb < 100 g/L) was seen in 20% of donors after harvest with median decrease in Hb of 19 g/L. Variables independently associated with anaemia after harvest included donor to recipient weight ratio ( P = 0.011), high collection volume ( P = 0.044) and female gender ( P = 0.023). Total nucleated cell and CD34 concentration in the final collected product were associated with the inverse of harvested marrow volume ( P < 0.001). Conclusions: Pre‐harvest anaemia should be corrected where possible particularly in female donors. Marrow collection volume should be minimised to reduce post‐harvest anaemia, optimise CD34+ cell number and improve nucleated and stem cell concentrations in the harvest product.